Priority areas of police bodies’ activity in ensuring the citizens’ rights in the conditions of martial law legal regime in Ukraine (Law and Safety, 2022)
The specifics of the activities of the police bodies regarding the protection of citizens' rights during the legal regime of martial law have been disclosed. The differences in the powers granted to police bodies in peacetime and during countermeasures against internal threats of martial law have been characterized. Factors, due to which the police authorities significantly reduced the number of administrative and criminal offenses, the commission of which prevailed in peacetime have been established.The general circle of citizens’ rights, which are violated during the operation of the legal regime of martial law as a result of active hostilities, occupation of certain regions and settlements, has been defined. Those rights of citizens whose duty to prevent violation, protection and restoration rests with police bodies have been systematized. The priority directions of the police authorities’ activities in ensuring the rights of citizens during martial law have been outlined, the emergence of which is due to the action of this legal regime introduced as a result of a full-scale invasion of the territory of our state. The peculiarities of the implementation of each of the selected directions have been characterized. Quantitative and qualitative indicators of the activity of individual police bodies and divisions in the field of protection of citizens’ rights during martial law have been presented. The specifics of the implementation of powers by police bodies to record and investigate war crimes, strengthening the evacuation mechanisms of the state, providing police services to all categories of the population, and paying increased attention by the police to the use of additional guarantees of protection and protection of citizens’ rights have been clarified. The need to develop effective algorithms for police actions in conditions of active hostilities and in de-occupied territories has been argued, in particular regarding: demining of territories and buildings by investigative-operational groups equipped with mobile forensic laboratories; identification of collaborators and sabotage groups; recording and documenting war crimes depending on their type; investigation of certain types of war crimes; implementation of measures of police custody, taking into account the significant increase in the number of persons who need such measures; inspections of vehicles on highways and roadblocks; searching for missing persons.
Keywords: legal regime; martial law; police; citizens’ rights; protection; defence; interaction; efficiency.